Peran GTRA dalam Pelaksanaan Reforma Agraria di Kabupaten Lampung Tengah - Zahril Trinanda Putra; Aristiono Nugroho; Ahmad Nashih Luthfi (Widya Bhumi, 2021)
The implementation of agrarian reform to date has not been maximized due to the existence of sectoral egos and lack of coordination between related sectors / ministries. The institutional formation of the GTRA is expected to be able to unite across sectors of the relevant ministries / institutions. In Central Lampung Regency there are many land issues on HGU land and transmigration land which will later become the priority location of the Agrarian Reform Land (TORA). The Central Lampung BPN target in 2020 as many as 3,000 plots of land will be distributed to the public. It is hoped that the existence of GTRA can support the achievement of these targets. This study aims to determine the role of GTRA, obstacles and how to overcome obstacles in implementing agrarian reform in Central Lampung Regency. The research method used is qualitative with a descriptive approach. The results showed that budget limitations and the existence of an institutional sectoral ego led to impeded implementation of asset management and access structuring. A strong commitment from all GTRA implementers is needed in carrying out all agrarian reform programs. If not, the GTRA will be the same as the previous institution which only changed its name.Keywords: Agrarian Reform, GTRA, TORA Intisari: Pelaksanaan reforma agraria sampai saat ini belum maksimal dikarenakan adanya ego sektoral dan kurangnya koordinasi antara lintas sektor kementerian/lembaga terkait. Pembentukan kelembagaan Gugus Tugas Reforma Agraria (GTRA) diharapkan mampu menyatukan lintas sektor kementerian/lembaga terkait. Di Kabupaten Lampung Tengah terdapat banyak permasalahan tanah pada tanah HGU dan tanah transmigrasi yang nantinya dijadikan lokasi prioritas Tanah Objek Reforma Agraria (TORA). Target BPN Kabupaten Lampung Tengah tahun 2020 sebanyak 3.000 bidang tanah akan direditribusikan ke masyarakat. Harapannya dengan adanya GTRA dapat mendukung capaian target tersebut. Penelitian ini bertujuan untuk mengetahui peran GTRA, kendala dan cara mengatasi kendala dalam pelaksanaan reforma agraria di Kabupaten Lampung Tengah. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Hasil penelitian menunjukan bahwa keterbatasan anggaran dan adanya ego sektoral kelembagaan menyebabkan terhambatnya pelaksanaan penataan aset dan penataan akses. Dibutuhkan komitmen yang kuat dari seluruh pelaksana GTRA dalam menjalankan seluruh program reforma agraria. Jika tidak maka GTRA akan sama saja dengan kelembagaan sebelumnya yang hanya berganti nama.Kata Kunci: Reforma Agraria, GTRA, TORA